Chemically-strengthenable light-absorbing glass and light-gated cover plate
Patent Information
- Application Number
- CN202310088037.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-09
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2043-02-09
AI Technical Summary
Existing light-absorbing glass is not strong enough for fiber optic imaging elements, making it difficult to meet the requirements for the fabrication of high-intensity light-gating covers. Furthermore, it is prone to crystallization during thermal processing, which affects imaging quality.
A high-strength optically selective cover plate is prepared by using a specific composition of light-absorbing glass, including SiO2, B2O3, Na2O, K2O, Al2O3, Li2O, BaO, Fe2O3, NiO, Co2O3, Cr2O3 and Nd2O3, through chemical strengthening treatment, thereby controlling the glass's coefficient of thermal expansion and crystallization properties.
The light absorption effect of light-absorbing glass in the 300-1000nm wavelength band was improved, and a high-strength light-selecting cover plate was prepared. When the thickness is 0.5mm, the transmittance is ≤5% in the 300-900nm range and ≤9% in the 900-1000nm range, and it has high impact resistance.
Smart Images

Figure CN118459086B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to an optical glass, and more particularly to a chemically strengthenable light-absorbing glass and a light-gating cover. Background Technology
[0002] Light-absorbing glass is an important type of optical glass, primarily used to absorb specific wavelengths of light, thereby improving the filtering performance of optical components. Its most typical application is as a light-absorbing filter in fiber optic imaging components, such as anti-halo input window glass. With the expansion of application areas, smart wearable devices are placing high-strength requirements on light-absorbing glass, depending on the specific application scenario. Therefore, not only must the light-absorbing glass absorb specific wavelengths of light more thoroughly, but the cover plates manufactured from it also need to possess high resistance to mechanical impact.
[0003] Meanwhile, for light-absorbing glass used to prepare filters and high-strength cover plates, the following basic requirements should also be met: (1) Good moisture resistance and stability to prevent the glass material and fiber imaging elements from being corroded by the humid atmospheric environment for a long time and affecting the imaging quality; (2) Excellent anti-crystallization performance, so that the glass material does not crystallize or separate phase during multiple heat processing of fiber imaging elements; (3) Compositional stability, light-absorbing glass usually contains a lot of coloring ions, which will greatly increase fiber loss and affect imaging quality once they diffuse into the fiber during heat processing.
[0004] Ordinary light-absorbing glass, with a thickness of 1 mm, has a transmittance of ≥10% in the visible light range, which is still relatively high. Light-absorbing glass developed for fiber optic imaging elements currently only exhibits a certain light absorption effect in the 400-900 nm visible light band. Chinese patent application CN102603185A discloses a light-absorbing glass containing 60-100 parts ferric oxide, 10-15 parts cobalt trioxide, 5-10 parts black nickel oxide, 10-15 parts manganese dioxide, and 5-10 parts cerium dioxide. This glass, with a thickness of 0.40±0.01 mm, has a spectral transmittance of ≤5% in the 430-900 nm wavelength range. Chinese patent application CN106772791A discloses a light-absorbing glass containing 0-15% Fe2O3, 0-5% Co2O3, 0-5% Ni2O3, and 0-5% MnO2 by weight. This glass, with a thickness of 0.3 mm, exhibits a light transmittance of ≤5% for 400-900 nm light. With the expansion of applications for fiber optic imaging elements, high strength requirements are being placed on light-absorbing glasses depending on the specific application scenario. Summary of the Invention
[0005] The main objective of this invention is to provide a chemically strengthened light-absorbing glass that improves the light absorption effect of light-absorbing glass in the 300-1000nm wavelength band and meets the fabrication process requirements of high-strength light-selecting cover plates.
[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows:
[0007] A chemically strengthenable light-absorbing glass comprises the following components: SiO2 content of 55–60 wt%; B2O3 content of 1–3 wt%; Na2O content of 7–12 wt%; K2O content of 5–8 wt%; Al2O3 content of 7–12 wt%; Li2O content of 3–7 wt%; BaO content of 0–2 wt%; Fe2O3 content of 5–10 wt%; NiO content of 1–2 wt%; Co2O3 content of 0–1 wt%; Cr2O3 content of 1–2 wt%; and Nd2O3 content of 0–2 wt%.
[0008] The present invention also provides a chemically strengthened light-absorbing glass comprising the following components: SiO2 and Al2O3, in a content of 62-70 wt%; Na2O and Li2O, in a content of 10-16 wt%; B2O3, K2O and BaO, in a content of 7-12 wt%; Fe2O3, in a content of 5-9 wt%; NiO, in a content of 1-2 wt%; Co2O3, in a content of 0-1 wt%; Cr2O3, in a content of 1-2 wt%; and Nd2O3, in a content of 0-2 wt%.
[0009] More preferably, the chemically strengthenable light-absorbing glass comprises the following components: SiO2 and Al2O3, in a content of 64 wt%; Na2O and Li2O, in a content of 12 wt%; B2O3, K2O and BaO, in a content of 11 wt%; Fe2O3, in a content of 8 wt%; NiO, in a content of 1.5 wt%; Co2O3, in a content of 0.5 wt%; Cr2O3, in a content of 1.5 wt%; and Nd2O3, in a content of 1.5 wt%.
[0010] This invention also provides a method for preparing a light-gating cover plate from light-absorbing glass, comprising the following steps:
[0011] (1) Preparation of light-absorbing glass preforms and high-transmittance transparent glass preforms:
[0012] Preparation of light-absorbing glass rods: Light-absorbing glass batch materials are prepared according to the composition of light-absorbing glass. The light-absorbing glass batch materials are melted to obtain light-absorbing glass liquid. After stirring and clarifying, a homogenized light-absorbing glass liquid is obtained. Then, after annealing, extrusion molding, cooling and solidification, rough annealing, and cutting, light-absorbing glass rods are obtained. The light-absorbing glass rods are then subjected to a secondary annealing, cutting, rounding, grinding, and polishing process to obtain light-absorbing glass preforms.
[0013] Preparation of high transmittance transparent glass preform: Replace the components of light-absorbing glass with the components of high transmittance transparent glass, and prepare a high transmittance transparent glass preform according to the method for preparing light-absorbing glass preforms described above.
[0014] (2) Preparation of light-absorbing glass pillars and high-transmittance transparent glass monofilaments:
[0015] Preparation of light-absorbing glass column: The light-absorbing glass preform is CNC drilled to obtain a light-absorbing glass column;
[0016] Preparation of high transmittance transparent glass monofilament: The high transmittance transparent glass preform is drawn into monofilament using an optical fiber drawing machine;
[0017] (3) Preparation of optical selection cover plate:
[0018] Preparation of monofilament sleeve column: After ultrasonic cleaning, the perforated light-absorbing glass column is matched with the drawn high-transmittance transparent monofilament to form a monofilament sleeve column.
[0019] Preparation of thin sheets: The monofilament sleeve is demolded after hot pressing, and then the thin sheets are obtained by cutting the head, rolling, slicing, flat grinding, fine carving and polishing.
[0020] Preparation of light-selective cover plate: The thin sheet is chemically strengthened in a nitrate solution of 15% NaNO3 and 85% KNO3 at 410-430℃ for 7-9h to obtain a high-strength light-absorbing glass and a high-transmittance transparent glass composition, namely, the light-selective cover plate.
[0021] The particle size of the light-absorbing glass batch is controlled between 200 and 500 micrometers. The melting temperature is 1400-1500℃ for 7-9 hours. After the light-absorbing glass melt is heated by 30-60℃, it is stirred with a blade for 6-8 hours. After being fully homogenized and clarified, the melting furnace is cooled to 1200-1300℃ and enters the annealing and forming stage. Before the light-absorbing glass melt is discharged, the resistance heating element is preheated so that the temperature of the discharge tube reaches 900℃-950℃.
[0022] The outer diameter of the monofilament is 3-9mm ± 0.01mm, and the length of the monofilament is 8-320mm.
[0023] The monofilament sleeve is demolded after being hot-pressed at a temperature of 670±10℃ for 30-50 minutes.
[0024] The sheet has an outer diameter of φ23-25mm, an inner diameter of φ2.4-7.2mm, and a thickness of 0.3-2mm.
[0025] The softening point temperature of the light-absorbing glass is 20-40°C lower than that of the high-transmittance transparent glass. The transition temperature Tg of the light-absorbing glass is 570-600°C, and the softening point temperature Tf is 650-670°C. It does not crystallize when held at 810-860°C for 2-3 hours.
[0026] The coefficient of thermal expansion of the light-absorbing glass is consistent with that of the high-transmittance transparent glass, with an average coefficient of thermal expansion of 88–98 × 10⁻⁶ at 25–300°C. -7 / ℃.
[0027] The present invention also provides an optically selective cover plate, which is prepared according to the method described above.
[0028] When the thickness of the optical fiber cover is 0.5 mm, the transmittance is ≤5% in the range of 300-900 nm and ≤9% in the range of 900-1000 nm.
[0029] The present invention provides another optical gating cover plate. According to the method, a high-transmittance transparent glass component is replaced with a colored glass component that transmits a specific wavelength to prepare a high-intensity light-absorbing glass and a colored glass component that transmits a specific wavelength. The resulting optical gating cover plate can achieve the function of gating a specific wavelength.
[0030] By employing the above technical solution, the present invention has at least the following advantages:
[0031] This invention addresses the problem of low strength in optical absorption and gating covers by providing an optical absorption glass suitable for the fabrication of optical gating covers. This glass improves the light absorption effect in the 300-1000nm wavelength range, meeting the fabrication process requirements for high-strength optical absorption covers and enabling the production of high-strength optical gating covers. When the optical gating cover is 0.5mm thick, its transmittance is ≤5% in the 300-900nm range and ≤9% in the 900-1000nm range; furthermore, at a thickness of 1mm, a 110g steel ball dropped freely from 10cm can withstand the impact without breakage.
[0032] The above description is merely an overview of the technical solution of the present invention. In order to better understand the technical means of the present invention and to implement it in accordance with the contents of the specification, the preferred embodiments of the present invention are described in detail below. Attached Figure Description
[0033] Figure 1This is a flowchart illustrating the fabrication process of the optically selected cover plate provided in an embodiment of the present invention.
[0034] Figure 2 This is a structural design drawing of the optical selection cover plate according to Embodiment 1 of the present invention;
[0035] Figure 3 This is a structural design drawing of the optical selection cover plate described in Embodiment 2 of the present invention;
[0036] Figure 4 This is a structural design drawing of the optical selection cover plate described in Embodiment 3 of the present invention;
[0037] Figure 5 This is a structural design drawing of the optical selection cover plate described in Embodiment 4 of the present invention;
[0038] Figure 6 This is a structural design diagram of the optical selection cover plate described in Embodiment 5 of the present invention.
[0039] In the picture:
[0040] 1: High transmittance transparent glass; 2: Light-absorbing glass. Detailed Implementation
[0041] To further illustrate the technical means and effects adopted by the present invention to achieve its intended purpose, the specific implementation methods, structures, features, and effects of the present invention will be described in detail below with reference to the accompanying drawings and preferred embodiments. In the following description, different "embodiments" or "embodiments" do not necessarily refer to the same embodiment. Furthermore, specific features, structures, or characteristics in one or more embodiments can be combined in any suitable form.
[0042] See Figure 1 The present invention also provides a method for preparing a light-gating cover plate from light-absorbing glass, comprising the following steps:
[0043] (1) Preparation of light-absorbing glass preforms and high-transmittance transparent glass preforms:
[0044] Preparation of light-absorbing glass rods: Light-absorbing glass batch materials are prepared according to the composition of light-absorbing glass. The light-absorbing glass batch materials are melted to obtain light-absorbing glass liquid. After stirring and clarifying, a homogenized light-absorbing glass liquid is obtained. Then, after annealing, extrusion molding, cooling and solidification, rough annealing, and cutting, light-absorbing glass rods are obtained. The light-absorbing glass rods are then subjected to a secondary annealing, cutting, rounding, grinding, and polishing process to obtain light-absorbing glass preforms.
[0045] Preparation of high transmittance transparent glass preform: Replace the components of light-absorbing glass with the components of high transmittance transparent glass, and prepare a high transmittance transparent glass preform according to the method for preparing light-absorbing glass preforms described above.
[0046] (2) Preparation of light-absorbing glass pillars and high-transmittance transparent glass monofilaments:
[0047] Preparation of light-absorbing glass column: The light-absorbing glass preform is CNC drilled to obtain a light-absorbing glass column;
[0048] Preparation of high transmittance transparent glass monofilament: The high transmittance transparent glass preform is drawn into monofilament using an optical fiber drawing machine;
[0049] (3) Preparation of optical selection cover plate:
[0050] Preparation of monofilament sleeve column: After ultrasonic cleaning, the perforated light-absorbing glass column is matched with the drawn high-transmittance transparent monofilament to form a monofilament sleeve column.
[0051] Preparation of thin sheets: The monofilament sleeve is demolded after hot pressing, and then the thin sheets are obtained by cutting the head, rolling, slicing, flat grinding, fine carving and polishing.
[0052] Preparation of light-selective cover plate: The thin sheet is chemically strengthened in a nitrate solution of 15% NaNO3 and 85% KNO3 at 410-430℃ for 7-9h to obtain a high-strength light-absorbing glass and a high-transmittance transparent glass composition, namely, the light-selective cover plate.
[0053] See Figures 2-6 A light-selective cover plate, wherein a high-transmittance transparent glass 1 and a light-absorbing glass 2 are provided with through holes, and a monofilament of the high-transmittance transparent glass 1 is disposed in the through holes.
[0054] In the light-absorbing glass of this invention, Fe2O3, NiO, Co2O3, Cr2O3, and Nd2O3 are glass coloring components, and Fe... 3+ NiO ions exhibit excellent light absorption properties, primarily concentrated in the infrared region; NiO is a good visible light absorber. 2+ It exhibits good absorption in the visible light region and also has absorption in the near-infrared region; Co2O3 has good light absorption in the near-infrared region; Cr2O3 is a good visible light absorber, and a small amount of Cr... 3+ It can induce characteristic absorption of ultraviolet light and has a good absorption effect in the visible light region; Cr2O3 is introduced in the form of K2Cr2O7, and Fe 3+ The ions work together to achieve a composite absorption effect; rare earth ions Nd 3+ The spectral characteristics and light absorption in glass are very stable, exhibiting strong absorption in the wavelength range of 300nm to 1000nm, and Nd... 3+ Strong absorption peaks are observed at 548 nm, 568 nm, and 588 nm, with a small amount of Nd. 3+It can achieve a composite absorption effect in glass.
[0055] The (Na2O+Li2O) / (SiO2+Al2O3) ratio used in the optical absorbing glass component of this invention, which is between 0.1 and 0.3, can achieve a good strengthening effect, enabling the optical fiber cover to meet the requirements of high mechanical impact resistance.
[0056] This invention provides a material basis for preparing high-strength optical fiber cover plates. The raw materials for the fiber cover plate are two types of glass materials: chemically strengthenable light-absorbing glass and high-transmittance transparent glass for optical fibers. The process involves drilling, drawing monofilaments, wire splicing, hot pressing, cutting, rounding, slicing, surface grinding, fine carving, and polishing to obtain thin fiber cover plate sheets. These sheets are then immersed in molten salt for ion exchange to obtain the high-strength optical fiber cover plate. The molten salt used in this invention includes NaNO3 and KNO3. During the ion exchange, the Li... + Na with the molten salt + The exchange rate and the Na of the light-absorbing glass + With the K of the molten salt + The ratio of the exchange rates is 4.5 to 6.0; the molten salt comprises 15% NaNO3 and 85% KNO3 by mass percentage; preferably, the ion exchange temperature is 420°C; the ion exchange time is 8 hours, and finally a reinforced optical fiber cover is obtained.
[0057] The chemically strengthenable light-absorbing glass of this invention comprises SiO2, Al2O3, Li2O, Na2O, K2O, B2O3, alkaline earth metal oxides, etc., with the selection of components and the effective ratio of each component within a reasonable range. This ensures that the thermal expansion coefficient, chemical stability, and thermal properties of the light-absorbing glass meet the preparation requirements of single-filament, multifilament, and hot-pressing processes, and improves the light absorption effect of the light-absorbing glass in the 300-1000nm wavelength band. The optical fiber cover plate prepared from the chemically strengthenable light-absorbing glass of this invention has the advantages of high resolution, high contrast, and high impact resistance.
[0058] The present invention uses a method of gradually increasing the content of coloring components such as Fe2O3, NiO, CoO, Cr2O3, and Nd2O3 in the glass to prepare light-absorbing glasses, as shown in Examples 1-5. The composition (wt%) of the light-absorbing glass in each example is shown in Table 1.
[0059] Table 1. Components (wt%) of each embodiment
[0060]
[0061] Example 1
[0062] According to the light-absorbing glass components in Example 1 in Table 1, the glass batch material is prepared, and the particle size of the batch powder is controlled between 200 and 500 micrometers. After melting at 1450°C for 8 hours, the glass melt is heated to 40°C and stirred with a paddle for 7 hours. After being fully homogenized and clarified, the melting furnace is cooled to 1250°C and enters the annealing and forming stage. Before the glass melt is discharged, the resistance heating element is preheated so that the temperature of the discharge tube reaches 920°C.
[0063] After the glass is discharged, it flows into an aluminum bronze forming mold that is cooled by air or water at the inlet end; the glass liquid is then drawn onto the conveyor belt of the continuous annealing furnace, and the conveyor belt pulls the glass liquid out of the forming mold. The glass liquid cools and solidifies during the movement of the mold.
[0064] After the glass is conveyed out of the forming mold, it enters the continuous annealing furnace for rough annealing. After the glass exits the traction annealing furnace, it is cut with a water gun to obtain a light-absorbing glass rod with a neat and smooth cross-section. After secondary annealing, cutting, rolling, grinding and polishing, a light-absorbing glass preform with an outer diameter of φ3 and a height of 200mm is obtained.
[0065] CNC drilling was performed on a light-absorbing glass preform with an outer diameter of φ33 and a height of 200mm to obtain a light-absorbing glass column with an outer diameter of φ33mm, an inner diameter of φ8.9mm, and a height of 100mm. Figure 2 As shown, the cylindricity tolerance of the drilled hole is <0.05mm, the hole diameter tolerance is ≤0.025mm, the hole wall roughness Ra is <0.01mm, and there are no micro-cracks or chipped edges on the surface.
[0066] The high-transmittance transparent glass comprises the following components: SiO2 content 78wt%; Al2O3 content 2wt%; B2O3 content 3.5wt%; MgO content 0.3wt%; CaO content 1.2wt%; Li2O content 0.7wt%; Na2O content 6.2wt%; K2O content 7.8wt%; F2 content 0.2wt%; and SnO2 content 0.1wt%. The forming process of the high-transmittance transparent glass is the same as that of light-absorbing glass. The high-transmittance transparent glass preform undergoes secondary annealing, rounding, grinding, and polishing processes to obtain a φ30×1500mm high-transmittance transparent glass preform. The high-transmittance transparent glass preform is then drawn into monofilaments with an outer diameter of 8.9mm±0.01mm and a length of 220mm using an optical fiber drawing machine.
[0067] After being perforated, the light-absorbing glass column is ultrasonically cleaned and then matched with a drawn high-transmittance transparent monofilament to form a monofilament sleeve column. The monofilament sleeve column is then demolded after being hot-pressed at 678℃ for 36 minutes. It is then cut, rolled, sliced, ground, finely carved, and polished to produce a thin sheet with an outer diameter of φ24.8mm, an inner diameter of φ7.05mm, and a thickness of 0.9mm. The thin sheet is then chemically strengthened at 420℃ for 8 hours in a nitrate solution containing 15% NaNO3 and 85% KNO3 to obtain a high-strength light-absorbing glass and high-transmittance transparent glass composite, i.e., a light-selective cover plate.
[0068] Example 2
[0069] According to the light-absorbing glass components in Example 2 of Table 1, the glass batch material is prepared, and the particle size of the batch powder is controlled between 200 and 500 micrometers. After melting at 1400°C for 7 hours, the glass melt is heated to 60°C and stirred with a paddle for 6 hours. After being fully homogenized and clarified, the melting furnace is cooled to 1200°C and enters the annealing and forming stage. Before the glass melt is discharged, the resistance heating element is preheated so that the temperature of the discharge tube reaches 950°C.
[0070] After the glass is discharged, it flows into an aluminum bronze forming mold that is cooled by air or water at the inlet end; the glass is then pulled onto the conveyor belt of the continuous annealing furnace, and the glass is pulled out of the forming mold by the conveyor belt. The glass cools and solidifies during the movement of the mold.
[0071] After the glass is conveyed out of the forming mold, it enters the continuous annealing furnace for rough annealing. After the glass exits the traction annealing furnace, it is cut with a water gun to obtain a light-absorbing glass rod with a neat and smooth cross-section. After secondary annealing, cutting, rolling, grinding and polishing, a light-absorbing glass preform with an outer diameter of φ3 and a height of 150mm is obtained.
[0072] CNC drilling was performed on a light-absorbing glass preform with an outer diameter of φ3 and a height of 150 mm to obtain a light-absorbing glass column with an outer diameter of φ3 mm, two internal holes with an inner diameter of φ6.2 mm, and a height of 150 mm. Figure 3 As shown, the cylindricity tolerance of the drilled hole is <0.05mm, the hole diameter tolerance is ≤0.025mm, the hole wall roughness Ra is <0.01mm, and there are no micro-cracks or chipped edges on the surface.
[0073] High-transmittance transparent glass and light-absorbing glass have the same coefficient of thermal expansion, with an average coefficient of expansion of 88–98 × 10⁻⁶ at 25–300℃. -7 / ℃, the softening point temperature is 20-40℃ higher than that of light-absorbing glass. Its forming process is the same as that of light-absorbing glass. The high-transmittance transparent glass preform is processed by secondary annealing, rounding, grinding and polishing to obtain a φ30×1500mm high-transmittance transparent glass preform. The high-transmittance transparent glass preform is drawn into a single filament with an outer diameter of 6.2mm±0.01mm and a length of 170mm using an optical fiber drawing machine.
[0074] After being perforated, the light-absorbing glass column is ultrasonically cleaned and then matched with a drawn high-transmittance transparent monofilament to form a double monofilament sleeve column. The monofilament sleeve column is demolded after being hot-pressed at 675℃ for 35 minutes. Then, it is cut, rolled, sliced, ground, finely carved, and polished to produce a thin sheet with an outer diameter of φ24.8mm, an inner diameter of φ5.0mm, and a thickness of 0.9mm. The thin sheet is chemically strengthened at 410℃ for 9 hours in a nitrate solution of 15% NaNO3 and 85% KNO3 to obtain a high-strength light-absorbing glass and high-transmittance transparent glass combination, namely the light-selective cover plate.
[0075] Example 3
[0076] According to the light-absorbing glass components in Example 3 of Table 1, the glass batch material is prepared, and the particle size of the batch powder is controlled between 200 and 500 micrometers. After melting at 1500°C for 9 hours, the glass melt is heated to 30°C and stirred with a paddle for 8 hours. After being fully homogenized and clarified, the melting furnace is cooled to 1300°C and enters the annealing and forming stage. Before the glass melt is discharged, the resistance heating element is preheated so that the temperature of the discharge tube reaches 900°C.
[0077] After the glass is discharged, it flows into an aluminum bronze forming mold that is cooled by air or water at the inlet end; the glass is then pulled onto the conveyor belt of the continuous annealing furnace, and the glass is pulled out of the forming mold by the conveyor belt. The glass cools and solidifies during the movement of the mold.
[0078] After the glass is conveyed out of the forming mold, it enters the continuous annealing furnace for rough annealing. After the glass exits the traction annealing furnace, it is cut with a water gun to obtain a light-absorbing glass rod with a neat and smooth cross-section. After secondary annealing, cutting, rolling, grinding and polishing, a light-absorbing glass preform with an outer diameter of φ3 and a height of 100mm is obtained.
[0079] CNC drilling was performed on a light-absorbing glass preform with an outer diameter of φ3 and a height of 100 mm to obtain a light-absorbing glass column with an outer diameter of φ3 mm, four internal holes with an inner diameter of φ4.9 mm, and a height of 100 mm. Figure 4 As shown, the cylindricity tolerance of the drilled hole is <0.05mm, the hole diameter tolerance is ≤0.025mm, the hole wall roughness Ra is <0.01mm, and there are no micro-cracks or chipped edges on the surface.
[0080] The high transmittance transparent glass uses the high transmittance transparent glass formulation of Example 1. Its molding process is the same as that of light-absorbing glass. The high transmittance transparent glass preform is processed by secondary annealing, rounding, grinding and polishing to obtain a φ30×1500mm high transmittance transparent glass preform. The high transmittance transparent glass preform is drawn into a single filament with an outer diameter of 4.9mm±0.01mm and a length of 120mm using an optical fiber drawing machine.
[0081] After being perforated, the light-absorbing glass column is ultrasonically cleaned and then matched with drawn high-transmittance transparent monofilaments to form a four-monofilament. The monofilament column is then demolded after being hot-pressed at 673℃ for 33 minutes. It is then cut, rolled, sliced, ground, finely carved, and polished to produce a thin sheet with an outer diameter of φ24.8mm, an inner diameter of φ3.8mm, and a thickness of 0.9mm. The thin sheet is then chemically strengthened at 420℃ for 8 hours in a nitrate solution of 15% NaNO3 and 85% KNO3 to obtain a high-strength light-absorbing glass and high-transmittance transparent glass composite, i.e., a light-selective cover plate.
[0082] Example 4
[0083] According to the light-absorbing glass components in Example 4 of Table 1, the glass batch material was prepared, and the particle size of the batch powder was controlled between 200 and 500 micrometers. After melting at 1480°C for 8 hours, the glass melt was heated to 50°C and stirred with a paddle for 7 hours. After being fully homogenized and clarified, the melting furnace was cooled to 1350°C and entered the annealing and forming stage. Before the glass melt was discharged, the resistance heating element was preheated so that the temperature of the discharge tube reached 930°C.
[0084] After the glass is discharged, it flows into an aluminum bronze forming mold that is cooled by air or water at the inlet end; the glass is then pulled onto the conveyor belt of the continuous annealing furnace, and the glass is pulled out of the forming mold by the conveyor belt. The glass cools and solidifies during the movement of the mold.
[0085] After the glass is conveyed out of the forming mold, it enters the continuous annealing furnace for rough annealing. After the glass exits the traction annealing furnace, it is cut with a water gun to obtain a light-absorbing glass rod with a neat and smooth cross-section. After secondary annealing, cutting, rolling, grinding and polishing, a light-absorbing glass preform with an outer diameter of φ3 and a height of 80mm is obtained.
[0086] CNC drilling was performed on a light-absorbing glass preform with an outer diameter of φ33 and a height of 80mm to obtain a light-absorbing glass column with an outer diameter of φ33mm, five holes with an inner diameter of φ4.45mm, one hole with an inner diameter of φ3.5mm, and a height of 80mm. Figure 5 As shown, the cylindricity tolerance of the drilled hole is <0.05mm, the hole diameter tolerance is ≤0.025mm, the hole wall roughness Ra is <0.01mm, and there are no micro-cracks or chipped edges on the surface.
[0087] The high transmittance transparent glass uses the high transmittance transparent glass formulation of Example 1. Its molding process is the same as that of light-absorbing glass. The high transmittance transparent glass preform is processed by secondary annealing, rounding, grinding and polishing to obtain a φ30×1500mm high transmittance transparent glass preform. The high transmittance transparent glass preform is drawn into monofilaments with outer diameters of 4.45mm±0.01mm and 3.50mm±0.01mm respectively using an optical fiber drawing machine. The length of the monofilament is 100mm.
[0088] After being perforated, the light-absorbing glass column is ultrasonically cleaned and then matched with drawn high-transmittance transparent monofilaments to form a five-monofilament. The monofilament column is then demolded after being hot-pressed at 672℃ for 34 minutes. It is then cut, rolled, sliced, ground, finely carved, and polished to produce a thin sheet with an outer diameter of φ24.8mm, an inner diameter of φ3.95mm, an inner diameter of φ3.1mm, and a thickness of 1mm. The thin sheet is then chemically strengthened at 430℃ for 7 hours in a nitrate solution of 15% NaNO3 and 85% KNO3 to obtain a high-strength light-absorbing glass and high-transmittance transparent glass composite, i.e., a light-selective cover plate.
[0089] Example 5
[0090] According to the light-absorbing glass components in Example 5 of Table 1, the glass batch material was prepared, and the particle size of the batch powder was controlled between 200 and 500 micrometers. After melting at 1450°C for 8 hours, the glass melt was heated to 40°C and stirred with a paddle for 7 hours. After being fully homogenized and clarified, the melting furnace was cooled to 1250°C and entered the annealing and forming stage. Before the glass melt was discharged, the resistance heating element was preheated so that the temperature of the discharge tube reached 920°C.
[0091] After the glass is discharged, it flows into an aluminum bronze forming mold that is cooled by air or water at the inlet end; the glass is then pulled onto the conveyor belt of the continuous annealing furnace, and the glass is pulled out of the forming mold by the conveyor belt. The glass cools and solidifies during the movement of the mold.
[0092] After the glass is conveyed out of the forming mold, it enters the continuous annealing furnace for rough annealing. After the glass exits the traction annealing furnace, it is cut with a water gun to obtain a light-absorbing glass rod with a neat and smooth cross-section. After secondary annealing, cutting, rolling, grinding and polishing, a light-absorbing glass preform with an outer diameter of φ3 and a height of 50mm is obtained.
[0093] CNC drilling was performed on a light-absorbing glass preform with an outer diameter of φ33 and a height of 50mm to obtain a light-absorbing glass column with an outer diameter of φ3mm, 12 holes with an inner diameter of φ2.6mm, one hole with an inner diameter of φ4.8mm, and a height of 80mm. Figure 6 As shown, the cylindricity tolerance of the drilled hole is <0.05mm, the hole diameter tolerance is ≤0.025mm, the hole wall roughness Ra is <0.01mm, and there are no micro-cracks or chipped edges on the surface.
[0094] The high transmittance transparent glass uses the high transmittance transparent glass formulation of Example 1. Its molding process is the same as that of light-absorbing glass. The high transmittance transparent glass preform is processed by secondary annealing, rounding, grinding and polishing to obtain a φ30×1500mm high transmittance transparent glass preform. The high transmittance transparent glass preform is drawn into monofilaments with outer diameters of 4.80mm±0.01mm and 2.60mm±0.01mm respectively using an optical fiber drawing machine. The length of the monofilament is 80mm.
[0095] After being perforated, the light-absorbing glass column is ultrasonically cleaned and then matched with drawn high-transmittance transparent monofilaments to form a multi-monofilament column. The monofilament column is then demolded after being hot-pressed at 672℃ for 32 minutes. It is then cut, rolled, sliced, ground, finely carved, and polished to produce a thin sheet with an outer diameter of φ24.8mm, an inner diameter of φ4.20mm, an inner diameter of φ2.35mm, and a thickness of 1.2mm. The thin sheet is then chemically strengthened at 420℃ for 8 hours in a nitrate solution of 15% NaNO3 and 85% KNO3 to obtain a high-strength light-absorbing glass and high-transmittance transparent glass composite, i.e., a light-selective cover plate.
[0096] Example 6
[0097] The preparation method is the same as in Example 4, except that the high-transmittance transparent glass is replaced with colored glass that transmits a specific wavelength. The colored glass that transmits a specific wavelength includes the following components:
[0098] The content of SiO2 is 62 wt.%, Al2O3 is 17 wt.%, Na2O is 13 wt.%, K2O is 1 wt.%, MgO is 4.2 wt.%, CaO is 2 wt.%, Nd2O3 is 0.2 wt.%, SnO2 is 0.4 wt.%, and Sb2O3 is 0.2 wt.%.
[0099] The high-transmittance transparent glass and the colored glass that transmits a specific wavelength can both be selected from commercially available high-transmittance transparent glass and colored glass that transmits a specific wavelength.
[0100] This invention involves a series of experiments conducted by improving the glass coloring components such as Fe2O3, NiO, CoO, Cr2O3, and Nd2O3 in optical absorbing glass. The transmittance values of each optical absorbing glass after the improvement were measured in the 300-1000nm wavelength range using an ultraviolet spectrophotometer. By comparing and analyzing the transmittance values of each test sample, the improved optical absorbing glass shows higher performance in ultraviolet, visible, and near-infrared light, and basically achieves optical insulation, thus meeting the requirements for use as a cover plate for high-strength optical absorbing fibers.
[0101] Transmittance testing was conducted using a UV-2600 UV-Vis spectrophotometer manufactured by Shimadzu Corporation of Japan, with a wavelength accuracy of ±0.1 nm. The transmittance of 0.5 mm glass samples from Examples 1-6 in the 300-1000 nm wavelength range was tested. The transmittance values of each test sample at 300 nm, 500 nm, 700 nm, 900 nm, and 1000 nm were compared and analyzed, as shown in Table 2. The transmittance of the light-absorbing glass in each example showed that with the increase of glass coloring components such as Fe2O3, NiO, CoO, Cr2O3, and Nd2O3 in the light-absorbing glass, the absorption effect of the light-absorbing glass on ultraviolet, visible, and near-infrared wavelengths was significantly enhanced, with the absorption effect approaching 90%-100%. By improving the glass coloring components such as Fe2O3, NiO, CoO, Cr2O3, and Nd2O3 in the light-absorbing glass, the absorption effect of the light-absorbing glass is significantly enhanced. The light-absorbing glass prepared in Examples 4 and 2 has a transmittance of less than 9%. This example makes the light-absorbing glass have excellent absorption effect on ultraviolet, visible and near-infrared light.
[0102] Table 2. Transmittance (%) of the light-absorbing glass obtained in each embodiment.
[0103]
[0104] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some modifications or alterations to the above-disclosed technical content to create equivalent embodiments without departing from the scope of the present invention. Any simple modifications, equivalent changes, and alterations made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the scope of the present invention.
Claims
1. A chemically strengthened light-absorbing glass, characterized in that, It includes the following components: SiO2 content 55-60 wt%; B2O3 content 1-3 wt%; Na2O content 7-12 wt%; K2O content 5-8 wt%; Al2O3 content 7-12 wt%; Li2O content 3-7 wt%; BaO content 0-2 wt%. It also includes the following components: SiO2 and Al2O3, with a content of 62-70wt%; Na2O and Li2O, with a content of 10-16wt%; B2O3, K2O and BaO, with a content of 7-12wt%; Fe2O3, with a content of 5-9wt%; NiO, with a content of 1-2wt%; Co2O3, with a content of 0-1wt%; Cr2O3, with a content of 1-2wt%; and Nd2O3, with a content of 0-2wt%.
2. The chemically strengthened light-absorbing glass according to claim 1, characterized in that, It includes the following components: SiO2 and Al2O3, with a content of 64wt%; Na2O and Li2O, with a content of 12wt%; B2O3, K2O and BaO, with a content of 11wt%; Fe2O3, with a content of 8wt%; NiO, with a content of 1.5wt%; Co2O3, with a content of 0.5wt%; Cr2O3, with a content of 1.5wt%; and Nd2O3, with a content of 1.5wt%.
3. The method for preparing a light-gating cover plate from light-absorbing glass according to claim 1 or 2, characterized in that, Includes the following steps: (1) Preparation of light-absorbing glass preforms and high-transmittance transparent glass preforms: Preparation of light-absorbing glass rods: Light-absorbing glass batch materials are prepared according to the composition of light-absorbing glass. The light-absorbing glass batch materials are melted to obtain light-absorbing glass liquid. After stirring and clarifying, a homogenized light-absorbing glass liquid is obtained. Then, after annealing, extrusion molding, cooling and solidification, rough annealing, and cutting, light-absorbing glass rods are obtained. The light-absorbing glass rods are then subjected to a secondary annealing, cutting, rounding, grinding, and polishing process to obtain light-absorbing glass preforms. Preparation of high transmittance transparent glass preform: Replace the components of light-absorbing glass with the components of high transmittance transparent glass, and prepare a high transmittance transparent glass preform according to the method for preparing light-absorbing glass preforms described above. (2) Preparation of light-absorbing glass columns and high-transmittance transparent glass monofilaments: Preparation of light-absorbing glass column: The light-absorbing glass preform is CNC drilled to obtain a light-absorbing glass column; Preparation of high transmittance transparent glass monofilament: The high transmittance transparent glass preform is drawn into monofilament using an optical fiber drawing machine; (3) Preparation of optical gate cover plate: Preparation of monofilament sleeve column: After ultrasonic cleaning, the perforated light-absorbing glass column is matched with the drawn high-transmittance transparent monofilament to form a monofilament sleeve column. Preparation of thin sheets: The monofilament sleeve is demolded after hot pressing, and then the thin sheets are obtained by cutting the head, rolling, slicing, flat grinding, fine carving and polishing. Preparation of light-selective cover plate: The thin sheet is chemically strengthened in a nitrate solution of 15% NaNO3 and 85% KNO3 at 410-430℃ for 7-9h to obtain a high-strength light-absorbing glass and a high-transmittance transparent glass composition, namely, the light-selective cover plate.
4. The method according to claim 3, characterized in that, The particle size of the light-absorbing glass batch is controlled between 200 and 500 micrometers. The melting temperature is 1400-1500℃ for 7-9 hours. After the light-absorbing glass melt is heated by 30-60℃, it is stirred with a blade for 6-8 hours. After being fully homogenized and clarified, the melting furnace is cooled to 1200-1300℃ and enters the annealing and forming stage. Before the light-absorbing glass melt is discharged, the resistance heating element is preheated so that the temperature of the discharge tube reaches 900℃-950℃. The outer diameter of the monofilament is 3-9mm, and the length of the monofilament is 8-320mm; The monofilament sleeve is demolded after being hot-pressed at a temperature of 670±10℃ for 30-50 minutes. The outer diameter of the thin sheet 23-25mm, inner diameter 2.4-7.2mm, thickness 0.3-2mm.
5. The method according to claim 3 or 4, characterized in that, The softening point temperature of the light-absorbing glass is 20-40°C lower than that of the high-transmittance transparent glass, and the transition temperature T of the light-absorbing glass is... g The softening point temperature is 570–600℃. f The temperature is 650-670℃, and no crystallization occurs when the temperature is kept at 810-860℃ for 2-3 hours.
6. The method according to claim 3 or 4, characterized in that, The coefficient of thermal expansion of the light-absorbing glass is consistent with that of the high-transmittance transparent glass, with an average coefficient of thermal expansion of 88–98 × 10⁻⁶ at 25–300°C. -7 / ℃.
7. A light-selecting cover plate, characterized in that, Prepared according to the method described in any one of claims 3-6.
8. The optical selection cover plate according to claim 7, characterized in that, When the thickness of the light-selecting cover plate is 0.5 mm, the transmittance of the light-absorbing glass is ≤5% in the range of 300-900 nm and ≤9% in the range of 900-1000 nm.
9. A light-selecting cover plate, characterized in that, According to the method of any one of claims 3-6, a high-transmittance transparent glass component is replaced with a colored glass component that transmits a specific wavelength to prepare a high-strength light-absorbing glass and a colored glass component that transmits a specific wavelength, i.e., a light-gated cover plate.
Citation Information
Patent Citations
Glass used for absorbing optical spectrum with wavelength being 430-900nm for optical fiber panel and preparation process thereof
CN102603185A
Low stray light crosstalk type optical fiber image transmission component and manufacturing method thereof
CN106772791A
Glass composition for production of glazing absorbing ultraviolet and infrared radiation
CN101155763A
Glass material
CN113754277A
